(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
This study was carried out to determine possible biochemical markers in children suffering from Plasmodium falciparum malaria and Protein-Energy Malnutrition in a Hospital setting in Western Kenya. Spectrophotometric assays of selected biochemical parameters namely, albumin, total proteins, glucose, glutamate oxaloacetate transaminase, glutamate pyruvate transaminase and bilirubin, were determined. The assays were done on serum samples obtained from children < 5 years of age admitted to the paediatric ward as well as outpatient clinics at Webuye District Hospital and Moi Teaching and Referral Hospital in Western Kenya suffering from either or both of the two disease conditions. Plasma albumin levels showed 33% of the children to be below the normal range and 40% above normal; mean total protein concentration was 56.0 mg/l; mean glucose concentration was 65 mmol/l, glutamate oxaloacetate transaminase and glutamate pyruvate transaminase concentrations were 9.0 and 5.9 µl/l respectively. Total bilirubin was 0.3 mg/dl while mean concentration for creatinine was 0.75 mg/dl. The biochemical markers studied did not show any unusual values at the time of the assays, but serum glucose and albumin levels showed potential as diagnostic markers for the two disease conditions.